Increasing the biomolecular relevance of cell culture practice - Raluca E. Ghebosu; Lawrence Hui; Joy Wolfram (Journal of Biomedical Science)
Abstract The biomolecular relevance of medium supplements is a key challenge affecting cell culture practice. The biomolecular composition of commonly used supplements differs from that of a physiological environment, affecting the validity of conclusions drawn from in vitro studies. This article discusses the advantages and disadvantages of common supplements, including context-dependent considerations for supplement selection to improve biomolecular relevance, especially in nanomedicine and extracellular vesicle research.